Preparation and Transformations of Acetophenone-Derived Enamino Ketones, BF2-β-Ketoiminates, and BF2-β-Diketonates - Helena Brodnik; Luka Ciber; Uroš Grošelj; Nejc Petek; Bogdan Štefane; Jurij Svete (Molecules)
A series of differently substituted β-enaminones 2a,b, 4a–i, 8a–d, and 9–13, their BF2-β-ketoiminate complexes 5a–d, and BF2-β-diketonate complexes 6a–d were prepared as model substrates for photochemical transformations. The attempted photochemical transformations of enaminones 2, 4, 8 and BF2-β-ketoiminate complexes 5 failed. On the other hand, irradiation of mixtures of BF2-β-diketonate complexes 6a–d and cycloalkanes with UV-A light (365 nm) gave the corresponding De Mayo reaction products 7a–f in 9–30% yields. The photochemical ring-expansion of acetyl tetralone-derived BF2-complex 6d gave novel diannulated cyclooctane derivatives 7e and 7f, which would be difficult to obtain using conventional cyclization methods.